Simulation of methane steam reforming in a catalytic micro-reactor using a combined analytical approach and response surface methodology. (28th June 2021) - Pourali, Mostafa; Esfahani, Javad Abolfazli; Sadeghi, Mohammad Amin; Kim, Kyung Chun; Gostick, Jeff
Abstract: In this study, a steady-state analytical model for heat and mass transfer in a 2D micro-reactor coated with a Nickel-based catalyst is developed to investigate microscale hydrogen production. Appropriate correlations for each species' net rate of production or consumption, mass diffusivity, and the heat of reactions are developed using a detailed reaction mechanism of methane steam reforming. The energy and species conservation equations are then solved for the reactive mixture coupled with the wall energy equation. Finally, the response surface methodology (RSM) is employed to study the effects of channel height, inlet velocity and temperature, wall thickness and conductivity, and external heat flux on CH4 conversion. It is found that the inlet gas temperature, among different parameters, has the most influence on the overall performance of the microchannel hydrogen production. Also, the maximum necessary heat of reforming reaction increases by 84% and 26% if the CH4 conversion changes from 50% to 60% and 60% to 70%, respectively. The developed analytical simulation can be a useful tool for designing experiments in micro-scale hydrogen production. Graphical abstract: Image 1 Highlights: A mathematical approach is developed to investigate microscale hydrogen production. Appropriate correlations for CH4 conversion and CO2 selectivity are proposed. The interaction between parameters is studied using response surface methodology. The mixture temperature is the most effective parameter in hydrogen production.